2017
DOI: 10.1016/s2095-3119(16)61590-3
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and translocation of organic pollutants in plants: A review

Abstract: Organic pollutants, such as polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans (PCDD/Fs), polychlorinated biphenyls (PCBs), antibiotics, herbicides, and bisphenol A (BPA), are commonly found in agricultural environments. They are released into the environment as a result of their use for human health purposes and for farm management activities, and are often discharged as waste-water effluents. Most of these organic pollutants are taken up by plants through roots and leaves, and when they ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(68 citation statements)
references
References 72 publications
3
56
0
1
Order By: Relevance
“…Although the common paradigm is that plants are not able to uptake hydrocarbons from the soil, our findings suggested that plants themselves may play a role in taking up a fraction (even small) of TPH into their tissues, in accordance with the evidence provided by many studies ( Hunt et al, 2019 and references therein). Our experiment showed that hydrocarbon translocation into the aerial part of plants is limited and fixation occurs mainly in roots ( Zhang et al, 2017 ), mainly due to the high molecular mass and hydrophobic properties. In our experiments the mycorrhizae colonization may have promoted the accumulation of hydrocarbons in plants roots, although this pathway represented only a partial fraction of their overall removal from soil.…”
Section: Discussionmentioning
confidence: 83%
“…Although the common paradigm is that plants are not able to uptake hydrocarbons from the soil, our findings suggested that plants themselves may play a role in taking up a fraction (even small) of TPH into their tissues, in accordance with the evidence provided by many studies ( Hunt et al, 2019 and references therein). Our experiment showed that hydrocarbon translocation into the aerial part of plants is limited and fixation occurs mainly in roots ( Zhang et al, 2017 ), mainly due to the high molecular mass and hydrophobic properties. In our experiments the mycorrhizae colonization may have promoted the accumulation of hydrocarbons in plants roots, although this pathway represented only a partial fraction of their overall removal from soil.…”
Section: Discussionmentioning
confidence: 83%
“…Thus, it is possible that all morphotypes of H. cupressiforme from the mountain habitats contained lower amounts of attracting or conversely higher amounts of repellent volatiles. Furthermore, with increasing altitude, there is a decline in the concentrations of organic pollutants in the mosses [ 79 ], which are generally toxic to plants [ 80 ], and this may therefore affect their attractiveness and palatability to herbivores.…”
Section: Discussionmentioning
confidence: 99%
“…), by means of which plant collects substances from various elements of the environment (e.g. soil and air) [65][66][67][68][69]. The calculations consider the number of sewage sludges used per year and the duration of application (90 days after the first application or 100 years after the first application with a time step of 10 years for each subsequent application).…”
Section: Plantsmentioning
confidence: 99%